KEAMANAN SIBER DAN KEPERCAYAAN NASABAH: PERAN PENGATURAN HUKUM DALAM EKOSISTEM DIGITAL - Fitria, Annisa; Sugeng, Sugeng (Lex Jurnalica, 2025)
AbstractThe digital transformation of the banking sector offers increased convenience but also amplifies cybersecurity risks. This study aims to analyze the relationship between cybersecurity and customer trust, while evaluating the role of legal regulation as a moderating variable within Indonesia’s digital banking ecosystem. Using a normative juridical approach and descriptive analysis through literature review and regulatory examination, the findings reveal substantial weaknesses in Indonesia’s legal system—ranging from regulatory substance and inter-agency coordination to law enforcement mechanisms. The 2023 ransomware attack on Bank Syariah Indonesia (BSI) illustrates the fragile legal accountability of financial institutions in protecting consumer data. Comparative analysis with Singapore and the European Union highlights the urgent need for Indonesia to adopt a more responsive, consumer-oriented, and technologically adaptive legal framework. The study recommends the enforcement of cybersecurity audits, mandatory incident disclosures, and the establishment of a dedicated supervisory body for cybersecurity in the financial sector.Keywords: cybersecurity, customer trust, digital banking regulation